Hukum Pengusahaan Sumber Daya Air Berbasis Keadilan Atas Hak Air - Ronny Winarno; Ardhiwinda Kusumaputra (Universitas Pendidikan Nasional, 2020)
The purpose of this paper is to examine the harmonization ofprotection of water rights and people's rights to water in theinterests of commercialization of water resources. The researchmethod used is the normative juridical method. The result of thisstudy is that in realizing a balance between the interests of watercommercialization and the fulfillment of people's rights to water,it is necessary to harmonize the law of exploitation of waterresources by providing protection of water rights in order to createwater availability and use of water that is just and moral. Keywords:Commercialization of water,protection of water rights,rights to water.